Feral Swine Commercial Slaughter and Condemnation at Federally Inspected Slaughter Establishments in the United States 2017–2019 - Akkina, Judy; Burkom, Howard; Estberg, Leah; Carpenter, Lydia; Hennessey, Morgan; Meidenbauer, Karen (Frontiers in Veterinary Science, 2021)
Feral swine populations in the United States (US) are capable of carrying diseases that threaten the safety of the domestic swine industry. Performing routine, near-real time monitoring for an unusual rise in feral swine slaughter condemnation will increase situational awareness and early detection of potential animal health issues, trends, and emerging diseases. In preparation to add feral swine to APHIS weekly monitoring, a descriptive analysis of feral swine slaughter and condemnations was conducted to understand the extent of commercial feral swine slaughter in the US at federally inspected slaughter establishments and to determine which condemnation reasons should be included. There were 18 establishments that slaughtered 242,198 feral swine across seven states from 2017-2019. For all establishments combined, feral swine accounted for 63% of slaughtered animals. A total of 12 types of condemnation reasons were noted: Abscess/Pyemia, Arthritis, Contamination, Deads, Emaciation, Gen. Miscellaneous, Icterus, Injuries, Metritis, Misc. Degen. & Dropsic Condition, Misc. Parasitic Conditions, Moribund, Nephritis/Pyelitis, Non-ambulatory, Pericarditis, Pneumonia, Residue, Sarcoma, Septicemia, Sexual Odor, Toxemia, and Uremia. Exploratory analysis was conducted to determine which condemnation reasons should be included for weekly monitoring. For most condemn reasons, weeks of unusually high condemnations were noted. For example, a period of high pneumonia condemnations occurred from December 2, 2018 through February 3, 2019 with a spike on January 6, 2019 and a spike in dead swine occurred on November 3, 2019. The environmental impacts of more limited quality food resources, seasonal variation in the pathogen(s) causing pneumonia, and harsher weather are suspected to have an impact on the higher condemnation rates of pneumonia and dead swine during the winter months. Based on condemnation frequencies and the likelihood of each enabling situational awareness and early detection of feral swine health emerging diseases, the following were selected for weekly monitoring: abscess/pyemia, contamination/peritonitis, deads, emaciation, injuries, miscellaneous parasitic conditions, moribund, pneumonia and septicemia. Detection of notable increases in condemnation reasons strongly suggestive of foreign animal or emerging diseases should contribute valuable evidence towards the overall disease discovery process when the anomalies are both confirmed with follow up investigation and combined with other types of surveillance.